Implementation of Assessment of Physical Education Learning Results on Junior High School Teachers - Yulianti, Mimi; Apriani, Leni; Makorohim, M. Fransazeli; Ameliana, Sri Rezeki; Jumadi, Jumadi (Department of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to determine the implementation of the assessment of physical education learning outcomes in public and private junior high schools in Siak Hulu district, Kampar regency. The research design used is descriptive quantitative.The population in this study were all physical education teachers in public and private Junior High Schools in Siak Hulu District, Kampar Regency that consisted of 9 schools with 19 physical education teachers. The sample of this study were all population all physical education teachers of public and private Junior High Schools in Siak Hulu distric, Kampar regency. The technique for selecting a sampling of this research was saturation sampling. The data was collected by distributing questionnaires as an instrument of this research to all samples. The data analysis technique used in this research presents descriptive statistics with percentages results. Based on data processing and data analysis, the researchers conclude that the assessment of learning outcomes of this study is approximately 87% average score with very good category.